NEGRI, A. (2021). Spinoza ayer y hoy. Buenos Aires: Editorial Cactus. - Jimenez Morales, Luis Alberto (Daimon Revista Internacional de Filosofia, 2024)
Reseña de NEGRI, A. (2021). Spinoza ayer y hoy. Buenos Aires: Editorial Cactus.